(untitled) - Plumb, John A. (Ames, 1999)
Infectious diseases are among the greatest constraint to the expansion and realisation of the full potential of aquaculture. This valuable reference text concentrates on the infectious viral and bacterial diseases most important in aquaculture, and also addresses their existence in natural environments. The author organises the viral and bacterial diseases of fish into groups or families that are most extensively cultured. Dr. Plumb creates a balance between diseases of warmwater, coolwater, and coldwater fishes, and presents information on important disease problems not only in North America, but also around the world.
Keywords: Fishes,Fish-culture; Infections